Functionality of the human antibody response to Candida albicans. Issue 1 (31st December 2021) - Wich, Melissa; Greim, Stephanie; Ferreira-Gomes, Marta; Krüger, Thomas; Kniemeyer, Olaf; Brakhage, Axel A.; Jacobsen, Ilse D.; Hube, Bernhard; Jungnickel, Berit
ABSTRACT: Candida albicans is a common commensal on human mucosal surfaces, but can become pathogenic, e.g. if the host is immunocompromised. While neutrophils, macrophages and T cells are regarded as major players in the defense against pathogenic C. albicans, the role of B cells and the protective function of their antibodies are less well characterized. In this study, we show that human serum antibodies are able to enhance the association of human THP-1 monocyte-like cells with C. albicans cells. Human serum antibodies are also capable of inhibiting the adherence and damage dealt to epithelial cells. Furthermore, human serum antibodies impair C. albicans invasion of human oral epithelial cells by blocking induced endocytosis and consequently host cell damage. While aspartic proteases secreted by C. albicans are able to cleave human IgG, this process does not appear to affect the protective function of human antibodies. Thus, humans are equipped with a robust antibody response to C. albicans, which can enhance antifungal activities and prevent fungal-mediated epithelial damage.